Mapping spatial PPs - Cinque, Guglielmo; Rizzi, Luigi, 1952- (New York ; Oxford : Oxford University Press, 2010)
This collection explores the internal structure of prepositional phrases, and finds that phrases composed of spatial prepositions, adverbs, and particles do not have different structures, but merely spell out different parts of the same articulated configuration.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Grammar, Comparative and general -- Prepositional phrases; Grammar, Comparative and general -- Syntax